Fast Track - Garwood, Julie (Penguin Group, 2014)
Cordelia Kane has always been a daddy's girl-her father raised her alone. So when he has a serious heart attack, Cordelia is devastated, and the emotion is only intensified by the confusion she feels when he reveals the shocking truth about her mother. Cordelia can't suppress her curiosity about the woman who gave birth to her, and when she discovers the answers to her questions lie in Sydney, Australia, she travels there to get them. Hotel magnate Aiden Madison is Cordelia's best friend's older brother. He's oblivious to the fact that she's had a crush on him for years. When he gets railroaded into taking her along to Sydney on his company jet, he unknowingly puts her life at risk . . .
Keywords: Fiction; Romance